Student Statistical Literacy as An Initial Study for Sekolah Siaga Kependudukan in Indonesia : A Systematic Literature Review - Wijayanti, Palupi Sri; Juandi, Dadang (Jurnal Paedagogy, 2024)
This study aims to analyze studies on statistical literacy skills in Sekolah Siaga Kependudukan (SSK). Statistical literacy skill is part of mathematical literacy skill which is an assessment of students' mathematical abilities. The method used was a Systematic Literature Review (SLR) of all research articles indexed in Scopus, Sinta, Google Scholar, Semantic, and ERIC in the period 2018-2023. The search strategy was adjusted to the selection criteria. It used the PRISMA protocol with study characteristics such as education level, year of publication, research method, sample size, journal indexer, and research location. Data analysis of this study was conducted in a quantitative descriptive manner. The results of this SLR study stated that research related to students' statistical literacy skills has relatively increased research trends over the past five years. The research database that has been published and is the result of SLR research shows that most journal indexers are Q2 rank Scopus and are dominated by qualitative research. The majority of research locations were carried out in Indonesia in accordance with the existence of the Sekolah Siaga Kependudukan, which only exists in Indonesia. Further research recommendations can accommodate statistical research and learning with collaborative modules and student activities so as to improve aspects of statistical literacy skills in the form of interpreting, communicating, evaluating, and making data-based decisions.